Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/acv.12560
|View full text |Cite
|
Sign up to set email alerts
|

High roadkill rates in the Dong Phayayen‐Khao Yai World Heritage Site: conservation implications of a rising threat to wildlife

Abstract: Road networks are increasing globally, and as such incur increased pressure on wildlife communities. Large‐scale road expansion and infrastructure development occurring throughout Asia (i.e. Belt and Road Initiative) will affect hundreds of threatened species, leading to an increase in wildlife‐vehicle collisions. However, only a limited number of studies have quantified road mortality within this threatened landscape. To rectify this, we monitored the spatial‐temporal patterns of vertebrate roadkill in the Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 74 publications
(76 reference statements)
1
26
1
Order By: Relevance
“…While our study found mammals were frequently hit on HW 12 in the rainy season, albeit not significantly different from other seasons, Collinson et al (2014) and Silva et al (2019) found mammals were more likely to be hit in hot and cold seasons, respectively. We doubted the high WVC rate of mammals, mostly bats and Rodentia on HW 12 in rainy season could correlate to the time of dispersal of juveniles that happened a few months after parturition in the late hot season.…”
Section: Taxonomic Composition Of Wildlife-vehicle Collisions On Hw 12contrasting
confidence: 88%
See 3 more Smart Citations
“…While our study found mammals were frequently hit on HW 12 in the rainy season, albeit not significantly different from other seasons, Collinson et al (2014) and Silva et al (2019) found mammals were more likely to be hit in hot and cold seasons, respectively. We doubted the high WVC rate of mammals, mostly bats and Rodentia on HW 12 in rainy season could correlate to the time of dispersal of juveniles that happened a few months after parturition in the late hot season.…”
Section: Taxonomic Composition Of Wildlife-vehicle Collisions On Hw 12contrasting
confidence: 88%
“…Our results explained spatial clusters of the wildlifevehicle collisions were similar to Silva et al (2019). Our results suggest two locations where mitigation measures should be implemented to reduce road mortality of amphibians, reptiles and small-and medium-sized mammals.…”
Section: Spatial Patterns Of Wildlife-vehicle Collisions and Hotspotssupporting
confidence: 76%
See 2 more Smart Citations
“…Utilisation of covered areas may also be tied to threat avoidance, as threats are known to influence animal movement [105,106]. In our study area, roads pose a major threat to many animals [107], and King Cobras routinely exit the protected area. Outside of the protected area, King Cobras fall victim to both direct [25] and indirect [108] human-caused mortality.…”
Section: Discussionmentioning
confidence: 99%